Low-bias RNA sequencing of the HIV-2 genome from blood plasma - James, K; de Silva, T; Brown, K; Whittle, H; Taylor, S; McVean, G; Esbjörnsson, J; Rowland-Jones, S (American Society for Microbiolog, 2018)
Accurate determination of the genetic diversity present in the HIV quasi-species is critical for the development of a preventative vaccine: in particular, little is known about viral genetic diversity for the second type of HIV, HIV-2. A better understanding of HIV-2 biology is relevant to the HIV vaccine field because a substantial proportion of infected people experience long-term viral control, and prior HIV-2 infection has been associated with slower HIV-1 disease progression in co-infected subjects. The majority of traditional and next generation sequencing methods have relied on target amplification prior to sequencing, introducing biases that may obscure the true signals of diversity in the viral population. Additionally, target-enrichment through PCR requires a priori sequence knowledge, which is lacking for HIV-2. Therefore, a target enrichment free method of library preparation would be valuable for the field. We applied an RNA shotgun sequencing (RNA-Seq) method without PCR amplification to cultured viral stocks and patient plasma samples from HIV-2 infected individuals. Libraries generated from total plasma RNA were analysed with a two-step pipeline: (1) de novo genome assembly, followed by (2) read re-mapping. By this approach, whole genome sequences were generated with a 28x-67x mean depth of coverage. Assembled reads showed a low level of GC-bias and comparison of the genome diversity on the intra-host level showed low diversity in the accessory gene vpx in all patients. Our study demonstrates that RNA-Seq is a feasible full-genome de novo sequencing method for blood plasma samples collected from HIV-2 infected individuals.